2010
DOI: 10.1002/yea.1825
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophenol stress affects aromatic amino acid biosynthesis—a genome‐wide study

Abstract: Chlorophenols are a class of chemicals commonly used in preservatives, disinfectants, algaecides, herbicides and pesticides. However, there is a growing evidence that these compounds are a threat to human health. This is alarming as many chlorophenols are common pollutants found in the global environment at potentially biohazardous levels. Despite chlorophenols being abundant, widely used and poisonous, we know relatively little about their mechanism of toxicity in eukaryotes. Thus, we performed genome-wide gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Previous studies have reported that 2,4-DCP affected aromatic amino acid biosynthesis (Yadav et al, 2011) and directly bound to proteins, to interfere with their conformation (Zhang et al, 2011), suggesting that 2,4-DCP may have a proteotoxicity that causes ER stress (Gardner et al, 2013). Our recent study using mouse embryonic fibroblasts has proven the hypothesis that 2,4-DCP induces ER stress (Zhang et al, 2014b).…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have reported that 2,4-DCP affected aromatic amino acid biosynthesis (Yadav et al, 2011) and directly bound to proteins, to interfere with their conformation (Zhang et al, 2011), suggesting that 2,4-DCP may have a proteotoxicity that causes ER stress (Gardner et al, 2013). Our recent study using mouse embryonic fibroblasts has proven the hypothesis that 2,4-DCP induces ER stress (Zhang et al, 2014b).…”
Section: Discussionmentioning
confidence: 64%
“…as well as by-products formed during chlorination of drinking water for disinfection [1][2][3]. Most of the CPs are recalcitrant to natural biotic and chemical degradation, and some are known toxins, mutagens, and carcinogens [4,5]. Their toxicity, recalcitrance, bioaccumulation, strong odor emission, and persistence can directly impact the health of humans and wildlife and have a potential threat through the contamination of water bodies [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…ER stress induced by organic pollutants is usually characterized by the up‐regulations of CHOP and Bip (Faria et al, ; Haberzettl et al, ; Chang et al, ). Previous studies reported that 2,4‐DCP could bind with protein to interfere its conformation (Zhang et al, ) and affect aromatic amino acid biosynthesis (Yadav et al, ), which hinted that 2,4‐DCP might have a proteotoxicity to cause ER stress. To prove this assumption, the expressions of Bip and CHOP were measured in this study, and our results showed that 2,4‐DCP significantly increased the expressions of these two ER stress markers both at mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%